2014
DOI: 10.1039/c4cp02541e
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of occurrence of different types of protonated base pairs in RNA: a quantum chemical study

Abstract: Protonated nucleobases have significant roles in facilitating catalytic functions of RNA, and in stabilizing different structural motifs. Reported pKa values of nucleobase protonation suggest that the population of neutral nucleobases is 10(3)-10(4) times higher than that of protonated nucleobases under physiological conditions (pH ∼ 7.4). Therefore, a molecular level understanding of various putative roles of protonated nucleobases cannot be achieved without addressing the question of how their occurrence pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 82 publications
3
35
0
Order By: Relevance
“…In negative mode, several phosphates are protonated by interactions with ammonium ions, leaving the rest deprotonated . The better‐defined IMS bands observed in positive mode suggest that nucleobase protonation restricts the number of potential conformers via stabilization of non‐canonical base‐pairing, in good agreement with previous theoretical studies . This is in contrast to certain broader bands in positive mode (i.e.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In negative mode, several phosphates are protonated by interactions with ammonium ions, leaving the rest deprotonated . The better‐defined IMS bands observed in positive mode suggest that nucleobase protonation restricts the number of potential conformers via stabilization of non‐canonical base‐pairing, in good agreement with previous theoretical studies . This is in contrast to certain broader bands in positive mode (i.e.…”
Section: Resultssupporting
confidence: 88%
“…52 The better-defined IMS bands observed in positive mode suggest that nucleobase protonation restricts the number of potential conformers via stabilization of non-canonical base-pairing, in good agreement with previous theoretical studies. 53,54 This is in contrast to certain broader bands in positive mode (i.e. bands D and L) which are indicative of less tightly folded conformers, similar to those previously observed in nESI-TIMS experiments on DNA structures.…”
Section: Theoretical Modelingsupporting
confidence: 83%
“…We have considered both the possibilities and have observed that (Figure 6 C, D, Table 2) , N3 protonated cytosine results in a nonplanar triple with lower interaction energy (-32.1 kcal/mol) whereas, the triple with adenine N7 protonation (-49.3 kcal/mol) is more stable. This is due to the fact that, although cytosine N3 is easier to protonate than adenine N7 protonation in solution, 68 protonation induced charge redistribution in cytosine disfavors hydrogen bonding interactions via O2 of cytosine. On the other hand, protonation at N7 of adenine favors the hydrogen bonding interactions via N6 of adenine 68 .…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
“…This is due to the fact that, although cytosine N3 is easier to protonate than adenine N7 protonation in solution, 68 protonation induced charge redistribution in cytosine disfavors hydrogen bonding interactions via O2 of cytosine. On the other hand, protonation at N7 of adenine favors the hydrogen bonding interactions via N6 of adenine 68 . Higher charge dipole interaction between neutral cytosine and protonated adenine, compared .…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
“…Halder et al have benchmarked the conventional formalisms for modeling the process of protonation and concluded that considering water as a proton donor might provide a physicochemically relevant picture of the relative order of protonation propensity of different sites of the nucleobases. Also, while availability of stabilization possibilities determine the feasibility of occurrence of protonated bases, their occurrence context and specific functional roles are important factors determining their occurrence propensities (Halder et al, 2014). Specifically, the protonation of adenine, adenosine, and adenine-containing nucleotides have been studied extensively in both gas and condensed phases by theoretical and experimental means (Russo et al, 1998;van Zundert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%